2007
DOI: 10.1271/bbb.70362
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast-Like Organelles Were Found in Enucleate Sieve Elements of Transgenic Plants Overexpressing a Proteinase Inhibitor

Abstract: SaPIN2a, a plant proteinase inhibitor from nightshade (Solanum americanum), was located to the enucleate sieve elements (SEs) of phloem. The expressed SaPIN2a in transgenic lettuce showed inhibition of plant endogenous trypsin- and chymotrypsin-like activities, suggesting that SaPIN2a can regulate proteolysis in plant cells. To further investigate the physiological role of SaPIN2a, we produced transgenic nightshade and lettuce plants overexpressing SaPIN2a from the cauliflower mosaic virus (CaMV) 35S promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Moreover, we could not observe any other PIdependent developmental phenotype that had been reported for other species. There was no significant difference in flower diameter (Sin et al, 2006), number of reproductive units (Zavala et al, 2004a), plant growth (Zavala et al, 2004a;Xie et al, 2007), or trichome morphology and density (Liu et al, 2006;Luo et al, 2009). As a consequence, we infer that the developmental importance of SPI2a and SPI2b differs between species.…”
Section: Spis Differ In Substrate Specificity But Play No Major Role mentioning
confidence: 81%
See 3 more Smart Citations
“…Moreover, we could not observe any other PIdependent developmental phenotype that had been reported for other species. There was no significant difference in flower diameter (Sin et al, 2006), number of reproductive units (Zavala et al, 2004a), plant growth (Zavala et al, 2004a;Xie et al, 2007), or trichome morphology and density (Liu et al, 2006;Luo et al, 2009). As a consequence, we infer that the developmental importance of SPI2a and SPI2b differs between species.…”
Section: Spis Differ In Substrate Specificity But Play No Major Role mentioning
confidence: 81%
“…However, in S. nigrum, we did not observe any effect on flower size and found that only 0.7 to 2.8% of the seeds were aborted or defective (see Supplemental Figure 3 online). Zavala et al (2004a) and Xie et al (2007) reported that silencing or ectopic overexpression of SPI genes can affect plant growth. In comparative growth experiments, we found no differences in plant height between wild-type and SPI-silenced plants (see Supplemental Figure 3 online).…”
Section: Silencing Spi2a and Spi2b Has No Clear Effect On Growth And mentioning
confidence: 99%
See 2 more Smart Citations
“…Zavala et al (2004) have shown that constitutive overexpression of trypsin PI (TPI) in transgenic Nicotiana attenuata incurred large fitness costs, resulting in a large reduction in growth rate, plant height and seed production. Overexpression of a sieve element-localized PI of Solanum americanum, SaPIN2a, also caused growth retardation in transgenic plants, which might be due to the impaired differentiation of sieve elements in transgenic plant phloem (Xie et al, 2007).…”
Section: Co-expression Of Proteinase Inhibitors In Plant Bioreactorsmentioning
confidence: 99%